2006
DOI: 10.1590/s1516-44462006005000028
|View full text |Cite
|
Sign up to set email alerts
|

La importancia de la detección y el tratamiento de los síntomas somáticos en pacientes latinoamericanos con depresión mayor

Abstract: La importancia de la detección y el tratamiento de los síntomas somáticos en pacientes latinoamericanos con depresión mayor The importance of detection and treatment of somatic symptoms in Latin American patients with major depression R e s u m e n Objetivo: La depresión mayor es una enfermedad caracterizada por la presencia tanto de síntomas mentales como somáticos, los cuales afectan en forma significativa los procesos diagnósticos y terapéuticos así como el pronóstico. Método: Usamos una búsqueda de artícul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 55 publications
0
2
0
2
Order By: Relevance
“…Screening materials developed and tested in diverse cultures and structured brief "checklists" that elicit CF components could help orient clinicians during the brief clinical intake. For example, physical manifestations of emotional distress are common among ethnic minority patients and patients suffering from PTSD as a group (Jenkins & Cofresi, 1998;Tamayo, Rovner, & Munoz, 2007) and would be an important way to screen for the consequences of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Screening materials developed and tested in diverse cultures and structured brief "checklists" that elicit CF components could help orient clinicians during the brief clinical intake. For example, physical manifestations of emotional distress are common among ethnic minority patients and patients suffering from PTSD as a group (Jenkins & Cofresi, 1998;Tamayo, Rovner, & Munoz, 2007) and would be an important way to screen for the consequences of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these strengths, there are some limitations worth noting. First, some research has shown that Latinx may display depression as somatically (Lewis-Fernandez et al, 2005;Tamayo et al, 2007), but the PROMIS survey that we administered did not assess physical manifestations of depression. Therefore, researchers should consider using more culturally sensitive assessments of depression and anxiety symptomology in future studies.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
“…Alrededor de la sexta parte de la población mundial ha tenido al menos un episodio depresivo mayor en algún momento de su vida [12]. En el continente Americano es la primera causa de discapacidad superando a la violencia y las enfermedades cardiovasculares [4].…”
Section: Distribución En Las Poblacionesunclassified